2004
DOI: 10.1074/jbc.m304777200
|View full text |Cite
|
Sign up to set email alerts
|

The Caveolin Scaffolding Domain Modifies 2-Amino-3-hydroxy-5-methyl-4-isoxazole Propionate Receptor Binding Properties by Inhibiting Phospholipase A2 Activity

Abstract: Activation of the enzyme phospholipase (PLA 2 ) has been proposed to be part of the molecular mechanism involved in the alteration of 2-amino-3-hydroxy-5-methyl-4-isoxazole propionate (AMPA) glutamate receptor responsiveness during long term changes in synaptic plasticity (long term potentiation). This study assesses the effect of the caveolin-1 scaffolding domain (CSD) on the activity of the regulatory enzyme PLA 2 . Caveolin-1 is a 22-kDa cholesterol-binding membrane protein known to inhibit the activity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 53 publications
4
35
0
Order By: Relevance
“…For example, activation of cPLA 2 is regulated by p38MAPK (Zhou et al 2003), p42MAPK (Lin et al 1993;Nemenoff et al 1993;Gordon et al 1996), CaMK II (Muthalif et al 2001), and PKC phosphorylation (Wijkander and Sundler 1991;Nemenoff et al 1993), and iPLA 2 activation is regulated by PKC phosphorylation (Underwood et al 1998;Akiba et al 1999). In turn, stimulation of PLA 2 activity (with the PLA 2 activator melittin) in the presence of Ca 2+ in rodent cortical and hippocampal slices as well as membrane preparations increased [ 3 H]AMPA and [ 3 H]glutamate binding to the AMPA receptor (Massicotte and Baudry 1990;Baudry et al 1991;Massicotte et al 1991;Tocco et al 1992;Catania et al 1993;Bernard et al 1995;Chabot et al 1998;Gaudreault et al 2004), whereas PLA 2 inhibition and the Ca 2+ chelator EGTA reduced agonist binding to AMPA (Bernard et al 1993(Bernard et al , 1995Catania et al 1993). Additionally, PLA 2 inhibition in rat hippocampal slices prevented Ca 2+ -dependent formation of LTP in the CA1 field as well as the increase of [ 3 H]AMPA binding to the AMPA receptor that characterizes LTP (Bernard et al 1994).…”
Section: Reduced Pla 2 Activity and Aβ Production In Cultured Cellsmentioning
confidence: 96%
“…For example, activation of cPLA 2 is regulated by p38MAPK (Zhou et al 2003), p42MAPK (Lin et al 1993;Nemenoff et al 1993;Gordon et al 1996), CaMK II (Muthalif et al 2001), and PKC phosphorylation (Wijkander and Sundler 1991;Nemenoff et al 1993), and iPLA 2 activation is regulated by PKC phosphorylation (Underwood et al 1998;Akiba et al 1999). In turn, stimulation of PLA 2 activity (with the PLA 2 activator melittin) in the presence of Ca 2+ in rodent cortical and hippocampal slices as well as membrane preparations increased [ 3 H]AMPA and [ 3 H]glutamate binding to the AMPA receptor (Massicotte and Baudry 1990;Baudry et al 1991;Massicotte et al 1991;Tocco et al 1992;Catania et al 1993;Bernard et al 1995;Chabot et al 1998;Gaudreault et al 2004), whereas PLA 2 inhibition and the Ca 2+ chelator EGTA reduced agonist binding to AMPA (Bernard et al 1993(Bernard et al , 1995Catania et al 1993). Additionally, PLA 2 inhibition in rat hippocampal slices prevented Ca 2+ -dependent formation of LTP in the CA1 field as well as the increase of [ 3 H]AMPA binding to the AMPA receptor that characterizes LTP (Bernard et al 1994).…”
Section: Reduced Pla 2 Activity and Aβ Production In Cultured Cellsmentioning
confidence: 96%
“…Our study provides evidence for ␤ 2 -AR-induced translocation of the cPLA 2 to platforms constituted of caveolae tightly connected to SR membranes. PLA 2 activity has been implicated in constitutive membrane trafficking (45); however, only one recent study reported the presence of the cPLA 2 in caveolin 1-enriched membrane fractions isolated from hippocampal preparations (46). Most caveolin-interacting proteins identified so far contain a caveolin-binding motif located within their enzymatically active catalytic site (41).…”
Section: Discussionmentioning
confidence: 99%
“…[32][33][34][35] PLA2 inhibitors block AMPAR-associated LTP, while increasing PLA2 activity enhances LTP. 34 PLA2 enhancement of LTP is halted by sequestering free AA, but not by removing calcium or blocking eicosanoid production.…”
Section: Memory Formation (Long-term Potentiation)mentioning
confidence: 99%